POLA GAYA HIDUP DALAM KEUANGAN KELUARGA (STUDI KASUS:UNIT KERJA INSTITUSI PENDIDIKAN SWASTA DI BANDUNG) - Ridwan S. Sundjaja; Budiana Gomulia; Dharma Putra Sundjaja; Felisca Oriana; Inge Barlian; Meilinda Meilinda; Vera Intanie Dewi (Research Report - Humanities and Social Science, 2011)
This research was conducted to determine lifestyle patterns in family finances. This research was conducted in a private educational institution in Bandung. Data collection technique used in this research is survey technique with questionnaires and for data analysis technique that used in this study is descriptive analysis. It has been found that the lifestyle patterns of employees at one of private educational institution in Bandung generally still have a good patterns.This is proved by the monetary sequences of their revenue and expense. Also, the priority selection of their needs and wants in fullfilling their life style is still in control.The result of this research, generally the respondents already have their own house, vehicles, and mobile communication devices like handphone, with purchasing frequency in 1 year mostly less than 2 times.Moreover, the respondents also already have a habit of saving/investing and insurance.T o fill their spare time, respondents prefer to gather with their family, go to mall with frequency in a month 1-4 times and also they do exercise. But, the problem that needs to be taken care of is how to handle their credit card/loans because a lot of respondents have routine spending of paying credit card installment/loans.From this research, also found that there is still a lack of awareness for making simple bookkeeping of their revenue and expense. Therefore to make them literate family finances, they need to follow a counseling and training about family finances. Even, they are suggested to follow the counseling and training with their family members.